Faktor yang Mempengaruhi Niat Berkelanjutan untuk Menggunakan Mobile Banking Dilihat dari Prespektif Expectation Confirmation Model - Lilis Nurhidayah; Dewita Puspawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of usefulness, confirmation and satisfaction on continuance intention to use mobile banking from the perspective of Expectation Confirmation Model (ECM). The method used in this research is a purposive sampling method with a sample of 155 respondents. The data used in this research uses primary data and data analysis use PLS-SEM with the SmartPLS 4.0. The result of this research show that usefulness has no effect on satisfaction, while confirmation has an effect on satisfaction. Usefulness and confirmation have no influence on continuance intention, while satisfaction has on influence continuance intention. Usefulness has no effect on continuance intention mediated by satisfaction, while confirmation has an effect on continuance intention mediated by satisfaction.